PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL SNOW BALL THROWING BERBANTUAN WORDWALL PADA MATERI PENGUKURAN PANJANG DAN BERAT DI KELAS III SDN 16 PADANG BESI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low mathematics learning outcomes of third-grade students at SDN 16 Padang Besi, particularly in length and weight measurement material, where 58% of students had not yet reached the mastery criteria. The primary issues were the teacher-centered approach, monotonous methods, and the lack of interactive learning media. The objective of this study is to describe the improvement in students' learning outcomes through the implementation of the Snowball Throwing model assisted by Wordwall. The research method used is Classroom Action Research (CAR) with the cycle model by Kemmis and McTaggart. The results indicate that the application of this model can significantly improve students' learning outcomes. In Cycle I, Meeting II, the average knowledge score reached 75.76 with a mastery percentage of 62%. This improvement continued in the following cycle along with enhancements in learning execution. The conclusion is that the Snowball Throwing model assisted by Wordwall is effective in increasing student engagement and mathematics learning outcomes in lower grades.